Features of renormalization of the electronic spectrum by confined phonons in a semiconductor nanostructure quantum dot-quantum ring - Hnidko, I.S.; Makhanets, O.M. (Journal of Thermoelectricity, 2024)
In the model of effective masses and rectangular potential energies for the electron and the model of the dielectric continuum for phonons, the theory of renormalization of the electronic energy spectrum by interaction with confined phonons in the semiconductor (GaAs/AlxGa1-xAs) nanostructure quantum dot – quantum ring is constructed. The renormalized energy spectrum was found using the Green's function method by solving Dyson's equation. Dependencies of partial and full shifts of the main electronic energy level in the long-wave spectrum region on the geometric parameters of the semiconductor nanostructure were analyzed. Bibl 16, Figs. 2.